Editorial - Pedro Soares Neves; Sergio Vicente (Cadernos de Arte Pública)
CAP Public Art Journal is an open source, regular scientific publication dedicated to Public Art - a cross disciplinary field, which supports research on the collective production of public space. 'Narration' and 'Memory' are the themes of the two first issues of CAP, the aim of these issues is to reflect upon the practices and proposals that summon the space and the public sphere into an art work. Either through the concepts and notions associated with them, either through the practices supported by the engagement of the public and its communities.